2022
DOI: 10.3390/microorganisms10081551
|View full text |Cite
|
Sign up to set email alerts
|

The Scenario of Ticks and Tick-Borne Pathogens of Sheep on a Mediterranean Island

Abstract: Ticks and transmitted pathogens constitute a major concern for livestock health/welfare and productivity for the Mediterranean region, often posing an important zoonotic threat. The aim of this study was to investigate the presence, infection intensity, and seasonality of ticks and tick-borne pathogens on the island of Lesvos in Greece, which was selected as a potential hotspot for their circulation. To this end, 101 sheep farms were visited over a tick activity season, and ticks, blood samples, and questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Khan et al (2022) attributed the lack of reports on babesiosis in small ruminants from Pakistan to insufficient numbers of undertaken studies as well as unknown status of Rhipicephalus microplus as a globally reported vector of babesiosis in the country. By the same token, the low prevalence rates of Babesia ovis in a Mediterranean Island was ascribed to the low numbers of the relevant vector Rhipicephalus bursa (Saratsis et al, 2022). Whereas, others stated that they could not find Babesia genome in hard tick samples collected from sheep in Sudan due to unsuitable DNA primers (El Imam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al (2022) attributed the lack of reports on babesiosis in small ruminants from Pakistan to insufficient numbers of undertaken studies as well as unknown status of Rhipicephalus microplus as a globally reported vector of babesiosis in the country. By the same token, the low prevalence rates of Babesia ovis in a Mediterranean Island was ascribed to the low numbers of the relevant vector Rhipicephalus bursa (Saratsis et al, 2022). Whereas, others stated that they could not find Babesia genome in hard tick samples collected from sheep in Sudan due to unsuitable DNA primers (El Imam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the studies on A. capra were mostly conducted in China, in a short time its presence has been revealed in 18 different countries including China (Liu et al 2012 ), South Korea (Seo et al 2018 ), Türkiye (Altay et al 2022a ), Kyrgyztan (Altay et al 2022b , c ), Malaysia (Koh et al 2018 ), Japan (Kawahara et al 2006 ), Iraq (unpublished data GenBank; ON872236), Iran (Staji et al 2021 ), India (Kumar et al 2023 ), Pakistan (Isaq et al 2022), France (Jouglin et al 2019 ), Sweeden (Grandi et al 2018 ), Portugal (unpublished data, GenBank; OK091153), Spain (Remesar et al 2022 ), Greece (Saratsis et al 2022 ), Angola (Barradas et al 2021 ), Morocco (Elhachimi et al 2021 ), and Ghana (Addo et al 2023 ) by molecular techniques (Fig. 1 ).…”
Section: The Molecular Prevalence Of Anaplasma Capramentioning
confidence: 99%